2006
DOI: 10.1161/circulationaha.105.546010
|View full text |Cite
|
Sign up to set email alerts
|

Are Drug-Eluting Stents Cost-Effective?

Abstract: Since their commercial introduction in 2003, drugeluting stents (DES) have rapidly altered the management of coronary artery disease. Before their development, the percutaneous management of coronary artery disease was performed predominantly by implantation of bare metal stents (BMS) made of either surgical stainless steel or metal alloys. Although such stents represented a considerable advance over balloon angioplasty alone, they remained limited by restenosis resulting from neointimal proliferation. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 49 publications
0
38
1
Order By: Relevance
“…It was estimated that, if drug-eluting stent were used, there would be an increment of R$9,524 per patient, with the cost per event avoided being over R$190,000. These figures were far higher than those described in other studies, probably because the target-vessel revascularization rate in the cohort with large vessels studied was as low as 5.8% 33 .…”
Section: Discussioncontrasting
confidence: 67%
“…It was estimated that, if drug-eluting stent were used, there would be an increment of R$9,524 per patient, with the cost per event avoided being over R$190,000. These figures were far higher than those described in other studies, probably because the target-vessel revascularization rate in the cohort with large vessels studied was as low as 5.8% 33 .…”
Section: Discussioncontrasting
confidence: 67%
“…6,7 In controlled trials among patients with complex lesions and high rates of BMS restenosis, formal economic evaluations have suggested that DES may be reasonably cost-effective. 8,9 On the other hand, studies involving broader populations have suggested that widespread adoption of DES may be a relatively inefficient use of scarce resources, particularly in healthcare systems outside the United States.…”
Section: Clinical Perspective P 961mentioning
confidence: 99%
“…Despite their established effectiveness in randomized controlled trials, the clinical and cost effectiveness of unrestricted DES use in routine practice has since been debated. [5][6][7][8] Given the financial consequences of widespread use of these more expensive stents, some health care systems introduced guidelines or encouraged restricted indications for DES use; such approaches have varied. [9][10][11][12] Against this background, abstracts presented at the World Congress of Cardiology (WCC) in September 2006 brought into question the safety of DES and, in particular, the complication of late stent thrombosis.…”
mentioning
confidence: 99%